Environmental & Financial Benefits of 360 kW Photo Voltaic Solar System (On-Grid) in University of Wah - Anwar, Khalid Mahmood; Riaz, Umar (Universitas Diponegoro, 2022)
In the 21st century, the utilization and application of renewable energy resources are the need of the hour. Currently, in Pakistan, the cost of electricity per unit is very high and it has a huge effect on financial matters. In this study, we have analyzed the 360 kW Photovoltaic (PV) Solar system (On-Grid) installed at the University of Wah, its effects on the financial aspects, and environment change before and after its installation and operation. There are many types of renewable energy resources but not all of them are environmentally friendly. The University of Wah opted for the PV Solar system because it is environmentally friendly with no carbon emissions and requires very less maintenance. In this paper, we have also discussed, how this system benefits the local community and benefits the environment. All the facts and statistics about the 360 kW PV Solar System (On-Grid) are shared in detail.Keyword: Photovoltaic solar panels, Electricity Demand, Renewable energy, Environmentally friendly, Climate change